THE EFFECT OF PRICE, PRODUCT QUALITY, SERVICE QUALITY, AND PROMOTION ON CUSTOMER LOYALTY OF SNOWHITE SKINCARE GRAND DEVINA BEAUTY CLINIC MALANG REGENCY - Tri Karahmawati; Kosasih; Ayu Laili Rahmiyati (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Background: Physical beauty has become a critical aspect for many women, driven by global trends and cultural influences. The demand for high-quality beauty services has led to increased competition among beauty clinics. Understanding factors that influence customer loyalty is crucial for clinics to maintain competitiveness. Aims: This study investigates the impact of price, product quality, service quality, and promotion on customer loyalty at Snowhite Skincare Clinic in Grand Devina, Malang. Research Method: A quantitative approach was used with a sample of 80 respondents selected from a total population of 100 Snowhite Skincare customers in Malang during October and November 2023. Data were collected using questionnaires, and secondary data were sourced from company records and industry analyses. Validity, reliability, and classical assumption tests were performed, followed by descriptive and verification analyses using multiple correlation techniques to examine the relationships between independent variables (price, product quality, service quality, promotion) and the dependent variable (customer loyalty). Results and Conclusion: The study found that price, product quality, service quality, and promotion significantly and positively affect customer loyalty. Improvements in these areas are linked to increased customer loyalty. Among the variables, product quality had the highest impact on loyalty. The findings suggest that Snowhite Skincare should enhance all four factors to boost customer satisfaction and loyalty effectively.   Contribution: This research provides valuable insights for beauty clinic managers in designing effective marketing strategies to improve customer retention and clinic competitiveness.